The emotions effect on a virtual characters design–A student perspective analysis - del Valle-Canencia, Marta; Moreno Martínez, Carlos; Rodríguez-Jiménez, Rosa-María; Corrales-Paredes, Ana (Frontiers in Computer Science, 2022)
Interaction between people and virtual characters through digital and electronic devices is a reality. In this context, the design of virtual characters must incorporate emotional expression at a non-verbal level looking for effective communication with the user. This exploratory study investigates the design features that an avatar functioning as a virtual assistant in educational contexts should have. From a multidisciplinary approach, the user’s research was elaborated by a semi-open questionnaire of self-perception of emotional characteristics, likeability, attractiveness, and applicability of a set of six 2D and 3D characters. The results extracted from a sample of 69 university students provide relevant information on design features and open new lines of future research. Aspects such as Ekman's basic emotion discrimination and the design of facial expression are analyzed. The incorporation of other body parts, their spatial orientation as well as contextual elements seem to contribute to effective emotional communication. The results also highlight how the design of a virtual character should take into consideration the complexity involved in facial gestures and changes in relation to the vertical axis and planes of movement. Finally, this article discusses the complexity involved in expressing a given emotion in a virtual character.